Pop songs as a creative learning tool to improve students’ listening abilities - Rahmat, Hery (Journal of English Language Proficiency, 2025)
Pop songs have been widely used to improve listening ability among students as alternative and creative tools in learning English. This study aims to explore students’ voice toward English pop songs usage to increase their listening abilities and to identify the challenges they face during the learning process. This is a descriptive qualitative method which use questionnaire and interviews given to an Indonesian state Islamic University students. The research found that most students use pop songs as a creative listening learning tool as it improves their listening. Moreover, they accept that pop songs enhance their pronunciation, intonation, as well as vocabulary. The students also admit that pop songs help them to become enjoy. In addition, English pop music enhances students’ mood and motivation. However, the students mention that there are some challenges appear during their learning namely understanding the fast tempos lyrics, the existence of unfamiliar words, ungrammatical lyrics, and obstacles in culture and religion for Muslim students. This study strengthen that English pop songs is a useful as well as creative tool for listening exercise, particularly as it is used collectively with proper teaching technique namely lyrics’ reading, listening repeatedly, as well as clear pronunciation songs’ selection.